Ecg Processing Algorithm in the Qrs Complex - Kaschel-Carcamo, H; Valencia-Cordero, C (IEEE, 2021)
This research shows the development of a novel algorithm for the processing of ECG (electrocardiograms) focused on the "QRS" complex, which measures the speed and acceleration of the heart rate based on the detection and generation of the "R" peaks. The objective is to establish a time window where the algorithm will run, allowing the early detection of arrhythmias in the heart rhythm, using few hardware and software resources, designed to be implemented in basic MCUs, performing an analysis in the time domain of the ECG. In addition, the design of an IIR filter of the Butterworth type is shown, specially designed for the elimination of Gaussian and Rayleight type noise, ensuring the obtaining of the "R" peaks of the "QRS" complex. The performance tests will be done with 5 ECG samples, four of them with medically normal ECG (Normal Sinus Rhythm), and one with atrial arrhythmia problems. This will ensure that the algorithm works, verifying that at large dispersions of heart rhythm accelerations it is possible to detect arrhythmias, in a simple processing system. Opening the way to the detection of arrhythmias based on the behavior of the acceleration of the heart rate.